Os estrangeiros são eles: redes de sociabilidade, lazer e empreendimentos entre imigrantes no bairro de Intermares – PB - Rêgo, Maktor Queiroz do (2020)
This work aims to analyze the networks of sociability, leisure and enterprises that are established among the residents of the Intermares neighborhood, in the city of Cabedelo (metropolitan region of the city of João Pessoa) in the state of Paraíba. This ethnography intends to report how cultural interactions are formed between two distinct cultures: The local culture (native) and the culture of immigrants (here called foreigners). The tensions resulting from this “cultural shock” and, consequently, the webs of interactions inherent to this reality, as well as its consequences in the formation of the neighborhood's identity, constitute themselves as subjects of this research. We use, as theoretical assumptions, contributions from authors affiliated to the fields of Cultural Studies and Urban Anthropology such as: Gilberto Velho, Nobert Elias, Stuart Hall, among others - who conceptualize the notions of identity and sociability, considering the relevance of these concepts in discourse and practices developed within the group of foreigners studied here. We approach these groups and social institutions, cultural processes and spatial dynamics in the contemporary urban context, with an emphasis on territorialities and discussions on urban requalification processes, as well as in the analysis of sociability, entrepreneurship and leisure networks. We understand that “foreigners” play an extremely relevant role in the social life of Intermares neighborhood - permanently resignifying its economic and cultural structure. As a corpus, we chose data collected during field observations and also audio and video recordings made during immersions in the research in question. This ethnography is basically structured in four chapters, where I discuss the cultural conflict in the neighborhood of Intermares-PB that is established between the native culture and the culture, which I refer to here, "foreign". In the first part, I try to demonstrate how the neighborhood is organized and structured, in addition to addressing the research subjects. In a second step, I describe the tensions between natives and foreigners, analyzing the relations that are established between foreigners and the local culture based on commercial relations. In the last part, I try to go deeper into the ethnic / racial and identity issues, in order to reach the conclusion about the profound cultural changes introduced in the neighborhood due to the presence of foreigners and their social / cultural / economic practices.